A Ship Traffic Disturbance Vulnerability Index for Northwest European Seabirds as a Tool for Marine Spatial Planning - Fliessbach, Katharina Leonia; Borkenhagen, Kai; Guse, Nils; Markones, Nele; Schwemmer, Philipp; Garthe, Stefan (Frontiers in Marine Science, 2019)
Ship traffic in Northwestern European seas is intense and continuing to increase, posing a threat to vulnerable seabird species as a result of disturbance. However, information on species-specific effects of ship traffic on seabirds at sea is limited, and tools are needed to prioritize species and areas to support the integration of conservation needs in Marine Spatial Planning. In this study, we investigated the responses of 26 characteristic seabird species in the German North and Baltic Seas to experimental ship disturbance using large datasets collected as part of the Seabirds at Sea counts. We developed a Disturbance Vulnerability Index (DVI) for ship traffic combining indicators for species’ shyness, escape costs, and compensatory potential, and analyzed the relationships among shyness, escape costs, and vulnerability. The DVI was calculated using the following eight indicators: escape distance, proportion of escaping birds, proportion of birds swimming prior to disturbance, wing loading, habitat use flexibility, biogeographic population size, adult survival rate, European threat and conservation status. Species-specific disturbance responses differed considerably, with common scoters (Melanitta nigra) and red-throated loons (Gavia stellata) showing the longest escape distances and highest proportions of escaping individuals. Red-throated loon,black guillemot (Cepphus grylle), Arctic loon (Gavia arctica), velvet scoter (Melanitta fusca), and red-breasted merganser (Mergus serrator) had the highest DVI values, and gulls and terns had the lowest. Contrary to theoretical considerations, shyness correlated positively with escape costs, with the shyest species also being the most vulnerable among the species studied. The strong reactions of several species to disturbance by ships suggest the need for areas with little or no disturbance in some marine protected areas, to act as a refuge for vulnerable species. This DVI can be used in combination with distribution data to identify the areas most vulnerable to disturbance.